Prawa człowieka prawem natury - źródło czy tożsamość? Refleksja nad koncepcją praw człowieka w cywilizacji Zachodu (Świat Idei i Polityki, 2010)
Nowadays among the most popular concepts which characterize Western Civilization undoubtedly at the forefront is the idea of Human Rights. Although the enthusiasts of the individual rights’s cult proclaim that their current perspective is the product of modern culture. There is no doubt that sources of Human Rights would have been traced back to Ancient Greek times, in the doctrines of natural law, which was obligatory at that time for everyone and everything. The aim of the article is to present the identity of natural law being the source of Human Rights. This unity firmly survived till the time of the Enlightenment, when the French Revolution and following it positivism destroyed religious connection of Western Civilization contributed to the re-evaluation of existing standards. Perhaps, the current belief in the social and technological progress, the development of the idea of democracy or free approach to human sexuality, force the opposite emphasis on the protection of individual rights as well as strictly legal – doctrinal, which is linked with the increasing number of the present conflicts between conservatism and liberalism.